2020
DOI: 10.1038/s41467-020-18616-0
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the static and dynamic responses of organic single-crystal field-effect transistors

Abstract: Transistors, the most important logic elements, are maintained under dynamic influence during circuit operations. Practically, circuit design protocols and frequency responsibility should stem from a perfect agreement between the static and dynamic properties. However, despite remarkable improvements in mobility for organic semiconductors, the correlation between the device performances achieved under static and dynamic circumstances is controversial. Particularly in the case of organic semiconductors, it rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 38 publications
3
39
0
Order By: Relevance
“…using similar devices have reported comparably low contact resistances, [36,37] leading to a concomitant enhancement in the on/off current ratio (up to 10 10 ) and the transit frequency (up to 45 MHz). [36] While analyses of the crystal structure suggested that the monolayer C 8 -DNBDT-NW crystals contained a higher density of packing defects that limited the TFT performance compared to the multilayer crystals, an additional factor that was not discussed is that the uppermost layer of the crystals may have degraded due to thermal damage during the deposition of the gold contacts (by thermal evaporation in vacuum). [61] To combat this potentially critical effect, the Chan group implemented mechanically transferred gold contacts gently placed onto large-area monolayer crystals of C 10 -DNTT (Figure 7a).…”
Section: Low-dimensional Liquid Crystals Of Small-molecule Semiconductorsmentioning
confidence: 95%
“…using similar devices have reported comparably low contact resistances, [36,37] leading to a concomitant enhancement in the on/off current ratio (up to 10 10 ) and the transit frequency (up to 45 MHz). [36] While analyses of the crystal structure suggested that the monolayer C 8 -DNBDT-NW crystals contained a higher density of packing defects that limited the TFT performance compared to the multilayer crystals, an additional factor that was not discussed is that the uppermost layer of the crystals may have degraded due to thermal damage during the deposition of the gold contacts (by thermal evaporation in vacuum). [61] To combat this potentially critical effect, the Chan group implemented mechanically transferred gold contacts gently placed onto large-area monolayer crystals of C 10 -DNTT (Figure 7a).…”
Section: Low-dimensional Liquid Crystals Of Small-molecule Semiconductorsmentioning
confidence: 95%
“…Complementary metal‐oxide semiconductors (CMOS) logic circuits lay the foundation of modern electronics, where both p‐type (hole transport) and n‐type (electron transport) unipolar transistors are usually obtained by controlled doping of intrinsic semiconductors. [ 1–3 ] However, as the device dimensions decrease the conventional doping process such as ion implantation becomes increasingly difficult, and the batch‐to‐batch discrepancy induces wide distribution of device performance. Moreover, building CMOS logics with discrete p‐ or n‐doped transistors complicates the device manufacturing process and limits the miniaturization of the circuits.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Recently, various groups have demonstrated the fabrication of OTFTs with switching operations at a few tens of a megahertz, [ 4–8 ] e.g., Sawada et al. [ 5 ] reported a solution‐processed organic single‐crystal transistor with f T = 45 MHz at 7 V; recently, Perinot et al. [ 8 ] also reported a solution‐processed organic transistor with f T = 160 MHz at 40 V. The recent achievements open a route for high‐frequency OTFTs, but they still need further optimizations in order to go toward industrial production (e.g., fabrication on flexible substrates).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, the OTFT community focused on improving the charge carrier mobility in organic semiconductor materials, which is nowadays in excess of 10 cm 2 V −1 s −1 . [ 3 ] Recently, various groups have demonstrated the fabrication of OTFTs with switching operations at a few tens of a megahertz, [ 4–8 ] e.g., Sawada et al. [ 5 ] reported a solution‐processed organic single‐crystal transistor with f T = 45 MHz at 7 V; recently, Perinot et al.…”
Section: Introductionmentioning
confidence: 99%